Mapping spatially distributed material properties in finite element models of plant tissue using computed tomography. (December 2020) - Stubbs, Christopher J.; Larson, Ryan; Cook, Douglas D.
Abstract : Plant tissues are often heterogeneous. To accurately investigate these tissues, methods to spatially map these tissue stiffness values onto finite element models are required. The aim was to study the feasibility of using specimen-specific computed tomography data to inform the spatial mapping of Young's modulus values on finite element models. Specimen-specific finite element models with mapped elastic moduli values were developed. The validation models predicted the structural response of the specimen tests within 11.0% of the physical test data. The ability of the models to accurately predict the force-displacement response of the specimen in a different test configuration was considered to be positive validation of the mapping approach. The existence of a model with accurate spatial distribution of material stiffnesses allows for investigations into the stress patterns within the rind and pith tissues. Typically, structural failure in transverse compression manifests as a crack that propagates in the pith along the line of load. In building detailed FEM analyses, we are able to investigate in more detail how the stress is distributed through the pith, and further investigate the causes of the stress concentrations that ultimately lead to the structural failure of the specimen. A method was developed for determining the relationship between computed-tomography intensity and the transverse elastic modulus in maize stalks. The mapping was used to accurately predict the response of each specimen thus indicating that the mapping relationship is appropriate for modelling and stress analysis activities. Highlights: CT scans can be used to map material properties onto maize finite element models.